Clinical Characteristics, Co-Mutations, and Treatment Outcomes in Advanced Non-Small-Cell Lung Cancer Patients With the BRAF-V600E Mutation - Qu, Jingjing; Shen, Qian; Li, Yuping; Kalyani, Farhin Shaheed; Liu, Li; Zhou, Jianya; Zhou, Jianying (Frontiers in Oncology, 2022)
Background: Limited treatment outcome data is available for advanced non-small cell lung cancer (NSCLC) patients with BRAF V600E mutations. In this multicenter study, we describe therapeutic options and survival outcomes for patients with mutated BRAF V600E. Method: This was a retrospective study in which BRAF V600E-mutated advanced NSCLC patients were retrospectively recruited between January 2015 and December 2021 and had their clinical characteristics, co-mutations, and treatment efficacy assessed. Results: Fifty-three patients with BRAF V600E-mutant advanced NSCLC were included in the study, of which 64.2% were non-smokers, and the BRAF V600E mutation was more prevalent in men (52.8%). In addition, 96.2% of the patients had adenocarcinoma, and most (96.2%) received first-line therapy (23.5% anti-BRAF), with a progression-free survival (PFS) and overall survival (OS) of 10.0 [95% confidence interval (CI): 1.5–36.0 months] and 24.0 months [95% CI: 3.0–53.0 months], respectively. Twenty-three patients (43.4%) received second-line treatment (39.1% anti-BRAF), and PFS and OS were 5.0 [95% CI: 1.0–21.0 months] and 13.0 months [95% CI: 1.5–26.0 months], respectively. BRAF and MEK-targeted therapy (dabrafenib plus trametinib) produced longer PFS compared with that of chemotherapy with or without bevacizumab as a first-line (NA vs. 4.0 months, P = 0.025) or second-line therapy (6.0 vs. 4.6 months, P = 0.017). NSCLC patients harboring driver oncogene mutations such as BRAF V600E, EGFR, or ALK should be treated using targeted therapies. Concurrent TP53 mutations were the most common, affecting 11.3% (n = 6) of the patients, followed by EGFR 19 Del (n = 5). Patients with concurrent mutations had shorter PFS (9.0 vs. 10.0 months, P = 0.875) and OS (14.0 vs. 15.0 months, P = 0.555) than those without these mutations. Conclusion: These results suggest that combined BRAF- and MEK-targeted therapy is effective in BRAF V600E-mutated advanced NSCLC patients. Dabrafenib and trametinib re-challenge is also an option for patients with BRAF V600E-mutated NSCLC.